Analytical Overview of Some Motivational Theories and Their Implications in Provision of Continuous Professional Development of Staff of Colleges of Education and Analogous Institutions (British Journal of Multidisciplinary and Advanced Studies, 2023)
Motivation is the fuel in the engine of all living things in energizing for work to be done. If ignored, sectors are bound to run into mediocrity and subsequent diminishing returns in productivity. The sector of education needs that vitamin called motivation more than any other sector. Colleges of Education in Ghana by Act 847, produce teachers to implement basic school curriculum of the country.  The competence of teachers produced by these Colleges depends largely on the complex element of motivation as catalyst for good work in training student teachers. This paper dilates the topical issues of motivation in provision of continuous professional development for staff of the Colleges of Education as a way of improving work in that sector of education and related in the country. The paper presents motivational activities in organism using the author’s construct, Atiku 2018 SGT-AFGTF Model. This is followed by presentation on analytical overview of some content and process motivational theories. Every analysis, its implications to the Colleges of Education system are presented. The conclusion to the discussions is that motivation is universally needed by all sectors of workers and that though some packages seem to be needed by all workers, individual differentiated needs need to be taking into consideration when considering motivation of various sectors to boost performance. It is recommended, among others, that monetary packages should cover all workers and all sectors should be provided with opportunity to upgrade.